Are sleep studies worth doing?. Issue 1 (1st July 2000) - van Someren, Vivienne; Burmester, Margarita; Alusi, Gus; Lane, Rod
Abstract : AIMS: To evaluate a sleep study service for children suspected of having sleep related upper airway obstruction (SRUAO). DESIGN: Prospective survey. SETTING: Paediatric and ear, nose, and throat clinics of the Royal Free Hampstead NHS Trust. SUBJECTS: Consecutively referred children with SRUAO symptoms. MAIN OUTCOME MEASURES: Sleep study data, referring clinician's impression, and completed symptom questionnaires. RESULTS: A total of 120 children (aged 6 months to 15.5 years) were studied. Study scores showed that 24 were classified as normal, 42 as mild, 33 as moderate, and 21 as severe SRUAO. In the 106 cases with matching data between clinician's impression and study score, 71 had good agreement, 18 were underestimated by the clinician, and 17 were over estimated. No cases reported as moderate or severe sleep apnoea by the study were referred by the clinician as normal. There were no important associations between parental symptom scores and sleep study scores. CONCLUSION: In children with suspected SRUAO, sleep studies do contribute to assessing the need for operation, the likelihood of postoperative respiratory failure, or as a baseline or outcome measure in intervention studies.